2022
DOI: 10.1186/s12863-021-01022-w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic pan-cancer landscape identifies CARM1 as a potential prognostic and immunological biomarker

Abstract: Background Belonging to the protein arginine methyltransferase (PRMT) family, the enzyme encoded by coactivator associated arginine methyltransferase 1 (CARM1) catalyzes the methylation of protein arginine residues, especially acts on histones and other chromatin related proteins, which is essential in regulating gene expression. Beyond its well-established involvement in the regulation of transcription, recent studies have revealed a novel role of CARM1 in tumorigenesis and development, but th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 60 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…Given that PRMT2/4 and BRD4 are commonly overexpressed in breast tumors and play a crucial role in breast cancer progression (50)(51)(52), we next investigated whether PRMT2/4-mediated methylation of BRD4 at 3R regulates its oncogenic function using two common breast cancer cell lines, MCF7 and MDA-MB-231, that have been frequently used in PRMT4-and BRD4-relevant studies (52)(53)(54)(55). Short hairpin RNA (shRNA)-mediated knockdown of PRMT2 or PRMT4 alone inhibits cell proliferation and colony formation, while codepletion of PRMT2/4 has an additive effect (Fig.…”
Section: Deficiency In Brd4-3r Methylation Attenuates Its Oncogenic F...mentioning
confidence: 99%
“…Given that PRMT2/4 and BRD4 are commonly overexpressed in breast tumors and play a crucial role in breast cancer progression (50)(51)(52), we next investigated whether PRMT2/4-mediated methylation of BRD4 at 3R regulates its oncogenic function using two common breast cancer cell lines, MCF7 and MDA-MB-231, that have been frequently used in PRMT4-and BRD4-relevant studies (52)(53)(54)(55). Short hairpin RNA (shRNA)-mediated knockdown of PRMT2 or PRMT4 alone inhibits cell proliferation and colony formation, while codepletion of PRMT2/4 has an additive effect (Fig.…”
Section: Deficiency In Brd4-3r Methylation Attenuates Its Oncogenic F...mentioning
confidence: 99%
“…The pan-cancer analysis is a comprehensive and systematic approach to investigating and assessing the function and mechanism of a specific gene in tumorigenesis. Using the TCGA database, several genes were identified that may have a role in human cancers, such as FGL1 [30], CARM1 [31], CBX [32], LCK [33], and MNX1 [34]. In the present study, we conducted a systematic analysis of SKP2 expression across a variety of tumor forms, and the results revealed that practically most tumor types overexpressed SKP2 ).…”
Section: Discussionmentioning
confidence: 74%
“…Using bioinformatic tool TIMER2, Qiu and others (2022) highlighted the molecular perspective on the role of CARM1, comparing its expression difference between various cancer types and corresponding normal tissues. In BCa higher expression level of CARM1 was noticed, bringing out its potential value in clinical prognosis ( Qiu et al, 2022 ). PRMT6 knockdown can significantly inhibit the growth of bladder cancer cell lines SW780 and RT4.…”
Section: Bladder Cancer (Bca)mentioning
confidence: 99%